Forecasting US ager structure and the future of social security : the impact of adjustements to official mortality schedules - Bennett, N. G.; Olshansky, S. J.
gráfs.
pp. 703-727
Keywords: Seguridad Social; Mortalidad; Ancianos; Analisis Demografico; Grupos de Edad; Promedio de Vida; Estados Unidos de America